2012
DOI: 10.1158/1078-0432.ccr-11-2967
|View full text |Cite
|
Sign up to set email alerts
|

Ganetespib (STA-9090), a Nongeldanamycin HSP90 Inhibitor, Has Potent Antitumor Activity in In Vitro and In Vivo Models of Non–Small Cell Lung Cancer

Abstract: Purpose We describe the anticancer activity of ganetespib, a novel non-geldanamycin heat shock protein 90 (HSP90) inhibitor, in non-small cell lung cancer (NSCLC) models. Experimental Design The activity of ganetespib was compared to that of the geldanamycin 17-AAG in biochemical assays, cell lines and xenografts, and evaluated in an ERBB2 YVMA-driven mouse lung adenocarcinoma model. Results Ganetespib blocked the ability of HSP90 to bind to biotinylated geldanamycin and disrupted the association of HSP90 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
112
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 148 publications
(123 citation statements)
references
References 55 publications
10
112
1
Order By: Relevance
“…3A and Supplementary Fig. S1), as previously reported (9,11,35,36), TAS-116 was more rapidly eliminated from retina (t 1/2 ¼ 3.4 hours) than the other HSP90 inhibitors (t 1/2 ¼ 7.1-19.1 hours), thereby demonstrating its lower retinal distribution profile (Fig. 3A and Supplementary Table S3).…”
Section: Tas-116 Shows Antitumor Activity Without Inducing Eye Injurysupporting
confidence: 82%
“…3A and Supplementary Fig. S1), as previously reported (9,11,35,36), TAS-116 was more rapidly eliminated from retina (t 1/2 ¼ 3.4 hours) than the other HSP90 inhibitors (t 1/2 ¼ 7.1-19.1 hours), thereby demonstrating its lower retinal distribution profile (Fig. 3A and Supplementary Table S3).…”
Section: Tas-116 Shows Antitumor Activity Without Inducing Eye Injurysupporting
confidence: 82%
“…While we cannot rule out a contribution of direct chaperone inhibitory effects by STA-12-8666, these were unlikely exerting a major influence as evidenced by the compounds' weak intrinsic HSP90 inhibitory activity, as well as the superior efficacy achieved when compared with irinotecan plus ganetespib combination therapy. Further evidence was provided by the comparatively weaker antiproliferative effects of STA-12-8666 on tumor lines in vitro relative to ganetespib, yet the robust tumor regressions seen in xenograft lung tumors in vivo exceeded ganetespibs' previously published antitumor activity in the same models (31,32). Thus, our findings clearly demonstrate that HDC-mediated delivery of an established cytotoxic agent can achieve dramatic improvements in efficacy over traditional clinical formulations for these agents and that the approach is not complicated by effects due to loss of HSP90 function.…”
Section: Discussionmentioning
confidence: 99%
“…We applied these fundamentals to establish a new drug delivery system termed HSP90 inhibitor-drug conjugates, or HDC, based on the property that small-molecule inhibitors of HSP90 are preferentially retained in tumor cells in contrast to their rapid clearance from the circulation and normal tissues (8)(9)(10)(11)(12). HSP90 is a highly conserved molecular chaperone that plays an indispensable role in regulating the maturation and functional stability of a vast repertoire of cellular client proteins (13).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, Hsp90a protein was one of 12 proteins used as a panel for lung cancer diagnosis, which were generated by a new aptamer-based proteomic analysis of 1,326 archived serum samples from four independent studies of NSCLC in long-term tobacco-exposed populations (16). Other previous studies showed the HSP90 inhibitor had a potent antitumor activity in in vitro and in vivo models of therapy against NSCLC (17,18). Our current study further demonstrates that detection of plasma Hsp90a protein could be useful as a biomarker for diagnosis of lung cancer and for therapeutic monitoring of responses of patients with lung cancer.…”
Section: Discussionmentioning
confidence: 99%